Heat Resistance of Probiotic Candidate Enterococcus faecalis R22B in Different Matrices - Shanti Dwita Lestari; Rinto Rinto; Indah S Wahyuni; Sherly Ridhowati; Wulandari Wulandari (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2021)
Fermented fish, including rusip and bekasam, contains lactic acid bacteria, some of which have probiotic properties. Considering the beneficial effect, the count of viable cells in probiotic carrier foods must be at least 106 CFU/g throughout the product shelf-life. The processing and storage condition significantly affect the viability of probiotics in carrier foods. This research was conducted to determine the heat resistance of probiotic candidate Enterococcus faecalis R22B isolated from rusip in three different media: bekasam, rusip, and physiological saline solution (NaCl 0.85%). E. faecalis R22B was heated in each medium at a temperature of 70 °C for 0, 2, 4, 8, and 12 min. The media characteristics showed differences within the parameters included pH values of 4.41-6.99; aw 0.67-0.92; moisture content 72.56-98.09%; ash content 0.69-12.32%; protein content 0-14.7%; fat content 0-0.84%; and carbohydrate content from 0-4.93%. The results showed that the difference in the heating medium had no significant effect (p0.05) on the heat resistance of the bacteria, as indicated by the D70 value. The required average heating time at 70 oC to decrease E. faecalis R22B cells by 1log10 (D70 value) in bekasam, rusip, and physiological saline media were 3.17, 3.29, and 3.55 min, respectively. Despite having a lower DT-value, the reduction of bacteria cells in three media heated at 70 oC showed no difference (p0.05); therefore, bekasam and rusip are suitable for probiotic carrier food.